The Effect of Guided Inquiry Model with Active-Reflective Dimensional Learning Style on High School Students’ Chemistry Learning Outcomes - Meida Esterlina Marpaung (Media Eksakta, 2023)
The mean values of MAN 2 Palu students on the topic of reaction rates in the last three years are low. The cause of low learning outcomes is learning that has not paid attention to students’ average learning styles. The learning model used in this study is a guided inquiry model with an active dimensional learning style. The research sample selection technique was purposive sampling by taking into account the average student learning outcomes. The research samples were 27 students in class XI MIA6 as an experimental class, learning with the model and class XI MIA4 with 27 students as a class, learning with a guided inquiry control model. The stages of the research were identifying students' learning styles in the experimental class, applying the ITG-Dia model in chemistry learning by observing attitudes and skills activities and ending with giving an evaluation. The results of the learning style assistance were obtained by 8 students with an active dimension style which were then distributed to each group before learning was carried out. The results of the experimental class research obtained an average altitude of 84.26 (very good); skills of 79.42 (good); learning outcomes of 83; n-gain of 0.78 (high). Control class observations obtained an average altitude of 85.93 (very good); skills 79,79,56 (good); learning outcomes 60.78; n-gain 0.50 (medium). The results of the t-test statistical analysis obtained t 13.12 and t 1.67. The results of the statistical analysis showed that there were significant differences in student learning in the experimental class and the control class. Based on statistical analysis, it can be concluded that the application of the active-reflective dimensional model affects increases students' chemistry learning outcomes.